Implementasi Predictive Maintenance Menggunakan Metode Infrared Thermography Pada Peralatan Listrik di PT Pertamina Hulu Mahakam - Aji Sayuthi Ramadhan; Mad Yusup; Diyaa Aaisyah Salmaa Putri Atmaja (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Predictive Maintenance is a maintenance activity that focuses on monitoring equipment conditions in real-time and analyzing data to predict potential failures before they occur, allowing repairs to be made in a timely manner before major damage occurs. One of the methods used in predictive maintenance is "Infrared Thermography” or use of technology thermal imaging technology. In the context of predictive maintenance, thermography can be used to identify problems that are not visible to the naked eye, such as poor electrical connections, excessive heat buildup, or damage to components that cause heat leakage The purpose of this study was to determine the implementation of Predictive Maintenance with Infrared Thermography method on electrical equipment at PT PHM. The method used in this research is the observation method with primary and secondary data collection. The results showed that the implementation of predictive maintenance with the Infrared Thermography method on electrical equipment and systems at PT PHM was effective in helping the company avoid unnecessary costs and improve operational efficiency. Predictive maintenance allows companies to perform maintenance to identify potential damage before it occurs and can take preventive action so as to reduce repair costs, and operational productivity.